Flowering in Hylocereus spp.: comparative analysis and self-incompatibility : Flowering in Hylocereus spp. (Agro Productividad, 2022)
Objective: To know the variables of the reproductive component of materials for manual cross-pollination purposes, for which the search for sexual synchrony is emphasized.Design/methodology/approach: Four materials were analyzed, two with white pulp and two with red pulp, about which it is unknown if they present sexual self-incompatibility, and the synchrony in flowering is also unknown. The flowering phase and the variables that can shed light on its reproductive behavior were analyzedResults: It was found that the red materials present strong hercogamy, they cannot self-fertilize. There is also no floral synchrony, but there is closeness between the date of anthesis in a pitahaya with white pulp and a red one, which would allow promoting cross-pollination.Study limitations /implications: Hylocereus spp. is consumed in a large part of the world and has acquired a very strong importance since the industrial demand is increasing; however, several of the genotypes used in commercial production in Mexico show low fruit set compared to high floral emission, which is considered self-incompatibility.Findings/conclusions: The presence of hercogamy, stronger in the red-fleshed materials, indicates the existence of sexual self-incompatibility, explaining the fact that the materials emit a large number of flowers, but do not achieve fruit setting.